A new endemic psyllid genus, Stevekenia gen. nov. (Hemiptera: Psylloidea, Triozidae), from the Hawaiian Islands with two new and rare species on threatened host plants in the endemic genus Nothocestrum (Solanaceae) - Percy, Diana M. (Zootaxa, 2017)
A new endemic psyllid genus from the Hawaiian Islands, Stevekenia gen. nov., is described. Two new species, both single island endemics, feed on host plants in the endemic genus Nothocestrum (Solanaceae). Stevekenia nothocestri sp. nov. is found on Nothocestrum longifolium on the island of Oahu and Stevekenia aiea sp. nov. is found on N. peltatum on the island of Kauai. The host plants are montane rainforest species and both are on the IUCN Red List of Threatened Species. In particular, N. peltatum, which is endemic to the island of Kauai, is considered critically endangered, and therefore a similarly endangered status for these host-specific insects is likely. Only a few specimens of each Stevekenia species have been found, suggesting occurrence at low abundance. The host plants survive either as isolated individuals or small fragmented populations, which may already constitute less than the required critical host plant density for the long term survival of this psyllid genus. Unique morphological characters distinguish Stevekenia from other Hawaiian genera, and the placement of this genus within Triozidae is discussed. Mitochondrial DNA barcodes for the new species are provided.